Combining left atrial appendage closure and catheter ablation for atrial fibrillation: 2-year outcomes from a multinational registry. Issue 2 (30th October 2019) - Phillips, Karen P; Romanov, Aleksandr; Artemenko, Sergey; Folkeringa, Richard J; Szili-Torok, Tamas; Senatore, Gaetano; Stein, Kenneth M; Razali, Omar; Gordon, Nicole; Boersma, Lucas V A
Abstract: Aims: Clinical practice guidelines do not recommend discontinuation of long-term oral anticoagulation in patients with a high stroke risk after catheter ablation for atrial fibrillation (AF). Left atrial appendage closure (LAAC) with Watchman has emerged as an alternative to long-term anticoagulation for patients accepting of the procedural risks. We report on the long-term outcomes of combining catheter ablation procedures for AF and LAAC from multicentre registries. Methods and results: Data were pooled from two prospective, real-world Watchman LAAC registries running in parallel in Europe/Middle-East/Russia (EWOLUTION) and Asia/Australia (WASP) between 2013 and 2015. Of the 1140 patients, 142 subjects at 11 centres underwent a concomitant AF ablation and LAAC procedure. The mean CHA2 DS2 -VASc score was 3.4 ± 1.4 and HAS-BLED score 1.5 ± 0.9. Successful LAAC was achieved in 99.3% of patients. The 30-day device and/or procedure-related serious adverse event rate was 2.1%. After a mean follow-up time of 726 ± 91 days, 92% of patients remained off oral anticoagulation. The rates of the composite endpoint of ischaemic stroke/transient ischaemic attack/systemic thromboembolism were 1.09 per 100 patient-years (100-PY); and for non-procedural major bleeding were 1.09 per 100-PY. These represent relative reductions of 84% and 70% vs. expected rates per risk scores. Conclusion: The long-term outcomes from these international, multicentre registries show efficacy for all-cause stroke prevention and a significant reduction in late bleeding events in a population of high stroke risk post-ablation patients who have been withdrawn from oral anticoagulation.